1985
DOI: 10.21236/ada453814
|View full text |Cite
|
Sign up to set email alerts
|

Optimization on Microcomputers: The Nelder-Mead Simplex Algorithm

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 0 publications
0
51
0
1
Order By: Relevance
“…In addition to examining different parameter values across a grid, the optimum parameters with respect to C 3 (θ) are estimated using the Nelder Meade simplex search algorithm [21,9]. Note that the topologies generated by the topology generators are random in a statistical sense, due to differing random seeds for each run.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to examining different parameter values across a grid, the optimum parameters with respect to C 3 (θ) are estimated using the Nelder Meade simplex search algorithm [21,9]. Note that the topologies generated by the topology generators are random in a statistical sense, due to differing random seeds for each run.…”
Section: Resultsmentioning
confidence: 99%
“…There is no guarantee that a descent direction will exist in the nonsmooth case, as the next example shows. Consider the following variant of the Dennis-Woods function [94]:…”
Section: The Effects Of Multiple Search Directions and Samplingmentioning
confidence: 99%
“…This function is continuous and strictly convex, but its gradient is discontinuous everywhere on the line x 1 = x 2 . In [94], it was shown that a modification of the Nelder-Mead simplex algorithm can fail to converge to the minimizer of f . Now consider a point of the form (a, a) T , with a = 0.…”
Section: The Effects Of Multiple Search Directions and Samplingmentioning
confidence: 99%
“…The Nelder-Mead simplex direct search algorithm implemented in MAT-LAB's fminsearch and described in New Computing Environments: Microcomputers in Large-Scale Computing (Dennis and Woods, 1987), goes through k iterations. It begins by sampling n + 1 time values, which we will refer to as x 1 , x 2 , · · · , x n+1 .…”
Section: The Nelder-mead Simplex Direct Searchmentioning
confidence: 99%